Pengurusan Fasiliti UiTM Permatang Pauh / Nurul Shuhadah Zulkefli - Zulkefli, Nurul Shuhadah (Faculty of Civil Engineering, 2019)
Provide optimum comfort to staff and students, to ensure maintenance is done from time to time in accordance with the needs of the campus, and there are no compromises in terms of safety and quality. PPF contributes to the development of the country through assist customers in delivering policy and service outcomes through strategic partner co-operation, standardization of processes and systems for the sake of delivering consistent results, providing effective and innovative asset and project management, developing human capital and new competencies, build harmonious relationships with the community, and preserving the environment in service delivery